2016
DOI: 10.1136/jnnp-2016-313976
|View full text |Cite
|
Sign up to set email alerts
|

Highly active immunomodulatory therapy ameliorates accumulation of disability in moderately advanced and advanced multiple sclerosis

Abstract: Objective: To evaluate variability and predictability of disability trajectories in moderately advanced and advanced multiple sclerosis (MS), and their modifiability with immunomodulatory therapy. Methods The epochs between Expanded Disability Status Scale (EDSS) steps 3.6, 4.6 and 6.6.5 were analysed. Patients with relapse-onset MS and having reached 6-month confirmed baseline EDSS step (3/4/6) were identified in MSBase, a global observational MS cohort study. We used multivariable survival models to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 29 publications
(38 reference statements)
8
35
0
Order By: Relevance
“…Recent studies suggest that patients experiencing relapses at EDSS ≥3.5 are less likely to recover vs those with relapses at lower EDSS levels . We can surmise that although relapses become less frequent in each 5 year epoch after onset, the severity of these events in our most vulnerable patients (later MS) points to an important treatment opportunity with our DMTs (lauded primarily for their ability to decrease the frequency and severity of early relapses).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent studies suggest that patients experiencing relapses at EDSS ≥3.5 are less likely to recover vs those with relapses at lower EDSS levels . We can surmise that although relapses become less frequent in each 5 year epoch after onset, the severity of these events in our most vulnerable patients (later MS) points to an important treatment opportunity with our DMTs (lauded primarily for their ability to decrease the frequency and severity of early relapses).…”
Section: Discussionmentioning
confidence: 87%
“…Interpreting similar results with a background assumption of a likely independence between the processes of acute attacks and slow worsening, one study of similar design concluded “relapses play an independent and significant role for worsening of MS.” However, given the presence of relapse free progression occurring at the same rate as relapse‐associated progression, the investigators in one study chose a cautious stance interpreting their results, concluding that relapses were not definitively shown to contribute to long‐term disability . Yet another recent study found a positive correlation between relapses and worsening throughout the course of MS, and proposed that methodological issues concerning relapse rates had obscured this issue in prior studies …”
Section: Discussionmentioning
confidence: 99%
“…Some of these limitations may be overcome by using much larger data sets collected through multicenter collaborations. 21 Such studies can address more detailed questions concerning long-term treatment responses to multiple different medications but are thus far rare. Even single-center longitudinal studies such as ours, performed in the treatment era, remain rare and may reveal important changes in the real-world experience of MS care.…”
Section: Discussionmentioning
confidence: 99%
“…Blue lines indicate the rates of transition between EDSS steps 0, 3 and 6, stratified into quintiles (both before and after EDSS 3). Marked variability in disability progression rates is apparent before and after EDSS 3 (based on the data presented in Lizak et al10 ). 15.…”
mentioning
confidence: 99%